Correlation between Stress Level and Learning Motivation of Pre-Clinical Medical Student in Faculty of Medicine Universitas Airlangga - Rieza Rizqy Alda; Budi Utomo; Helmia Hasan (Faculty of Medicine Universitas Airlangga, 2020)
Introduction: Stress is mental health problem that can occur to medical student. Stress distract student’s life from student’s task. This distraction causes ineffective study. Ineffective study could cause lower motivation and probability of educational failure. Methods: This study was a cross-sectional analytic that used pre-clinical medical student in Faculty of Medicine Universitas Airlangga as population. This study used convenience/haphazard sampling as sampling method. The data was taken at Faculty of Medicine Universitas Airlangga from June to August of 2018. The subjects that meet the criteria were subjects who agreed to informed consent. The data was taken using questionnaires. The questionnaires were DASS (Depression Anxiety Stress Scales) and MSLQ (Motivated Strategies of Learning Questionnaire). The data then was examined for normality. Results: A total of 95 medical students were included in this study, 55 subjects were female, mostly aged 21 years old. Most of pre-clinical medical student’s stress level was on normal level (47.5%), while their motivation level was on adequate level (74.7%). Conclusion: There is a correlation between stress level and learning motivation of pre-clinical medical student in Faculty of Medicine Universitas Airlangga